'Effect of yarn composition and fabric weave design on microwave and EMI shielding properties of hybrid woven fabrics'. Issue 9 (2nd September 2022) - Gupta, Krishna Kumar; Abbas, Sayed M.; Abhyankar, Ashutosh C.
Abstract: Ring spun composite yarn (RCY; 755 denier) with linear resistance of 172 Ω/m is prepared with stainless steel (SS) fibre and polyester fibre in ratio of 80%: 20% (w/w). Sheath core yarn system, core being ring spun yarn and PET fibre as sheath material is prepared in various fibre compositions adopting friction spinning technique. For microwave interaction and EMI shielding, hybrid woven fabrics are prepared using sheath-core yarn in weft and SS/PET blended yarn (20% SS/80% PET) in warp in cell structured and rib structured weave design. Samples of woven fabric were evaluated for microwave and EMI shielding properties in frequency range of 8.2–18.0 GHz in parallel and perpendicular polarisation of electromagnetic wave (em wave). Samples having conducting yarn in warp and weft both have shown high reflection in both polarisation of em wave. Sample containing metal fibre content of 32.58% (w/w) prepared in cell-structured weave design containing 1330 and 2017 denier sheath-core yarn in weft and 165 denier (20% SS/80% PET) blended yarn in warp offered reflection of 89.4922–59.9864% in parallel mode and 92.8135–80.0789% in perpendicular mode. This offered EMI shielding of −30.9601 to −35.4659 dB in perpendicular and −17.0209 to −11.2131 dB in parallel mode in 8.2 − 18.0 GHz. Woven fabrics are highly breathable, its air permeability lies in the range of 22.5–26.2 ft 3 /ft 2 /s. It inherits high aesthetic values. This hybrid woven fabric finds potential applications in radar camouflage, protection of human being from hazardous effect of microwaves, EMI shielding and electrostatic discharging cover materials, etc.